Comparison of structure and function of human erythrocyte and human muscle actin. - Nakashima, K (1979)
Human erythrocyte actin and human skeletal muscle actin were purified by acetone powder extraction and gel filtration. Pure human erythrocyte actin resembles muscle actin in its polymerization and depolymerization by phalloidin, cytochalasin B, and DNase I, in its peptide mapping pattern, and in the amino acid composition of corresponding peptides. Isoelectric focusing gel analysis showed that human erythrocyte actin exists in the beta/gamma form, but muscle actin is in the alpha form. Abnormal deformability of resealed erythrocyte membranes was observed after incorporation of the actin-specific agents, phalloidin and DNase I, suggesting that erythrocyte actin might function as a membrane structural element to maintain erythrocyte membrane deformability.